Perioperative management of awake craniotomy: Role of anesthesiologist - Chayanika Kutum; Prashant Lakhe; Uzma Begum (Asian Journal of Medical Sciences, 2024)
Awake craniotomy is performed for resection of lesions located within or close to the eloquent areas of the brain. Both asleep-awake-asleep technique and conscious sedation have been used effectively for awake craniotomies, and the choice of optimal anesthetic regime is mainly as per the preferences of the anesthesiologist and surgical team. Propofol, remifentanil, dexmedetomidine, and scalp nerve block have been used successfully for intraoperative brain mapping. Appropriate patient selection, adequate perioperative psychological support, and proper anesthetic management for patients in every stage of surgery are essential for the safety and success of the surgery.